PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB MELALUI LINKTREE PADA MATERI POKOK BANGUN DATAR DI KELAS V SD NEGERI 065853 - Winda Septiana Sianturi; Elvi Mailani; Syahrial; Andri Kristianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop web-based Mathematics learning media through linktree on flat shape material in fifth grade elementary school and to determine the level of validity, practicality, and effectiveness. This study uses a 4D development model (Define, Design, Development, Disseminate). The subjects of the study were 20 fifth grade students of SDN 065853 Denai. Data collection techniques were interviews, observations, questionnaires, and tests. Data analysis techniques were carried out using qualitative and quantitative analysis. The results of the study showed that (1) web-based learning media through linktree was declared valid with the validation results of material experts of 82.2% and media experts of 92.7% with the criteria of "very feasible"; (2) linktree learning media was declared practical based on teacher responses with a percentage of 90% included in the criteria of "very practical"; and (3) linktree learning media was declared effective, indicated by the increase in student learning outcomes, where the average pre-test score of 46.75% increased to 87.00% in the post-test. In addition, at the dissemination stage, an increase was obtained from 47.3% to 86.7% with an N-Gain value of 0.76 or 76% which is included in the high category. Thus, web-based learning media through linktree is proven to be valid, practical, and effective for use in learning Mathematics on Flat Shapes in elementary schools and is able to significantly improve student learning outcomes.